Botswana : Systematic Country Diagnostic - World Bank Group (World Bank, Washington, DC, 2015)
Botswana has been one of the worlds fastest growing economies over the past 50 years, allowing the country to move from being among the poorest to upper middle income status - this has had the effect of pulling the majority of the population out of poverty. While Botswana is rightly praised for its management of resource wealth, it is apparent that the high levels of investment by government (in health, education, and infrastructure) are not delivering quality outcomes, making it increasingly difficult to meet the objectives of growth, diversification, and poverty elimination. Indeed, some of the foundations which drove the development success of Botswana over the past half century are being eroded or face risks. In this context, this systematic country diagnostic (SCD) is intended to assess the priorities for Botswana to make rapid progress in achieving the objectives of: (i) elimination of extreme poverty on a sustainable basis; and (ii) ensuring shared prosperity by improving the welfare of the less-well-off in the country. It includes individual chapters analyzing the opportunities and challenges to meeting these objectives with respect to: growth; inclusiveness; and sustainability. The SCD concludes with a prioritization of the key challenges.